Flotation-Assisted Homogenous Liquid–Liquid Microextraction for Determination of Cadmium in Vegetables. Issue 3 (3rd May 2016) - Khajeh, Mostafa; Saravani, Farahnaz; Ghaffari-Moghaddam, Mansour; Bohlooli, Mousa
ABSTRACT: Cadmium (Cd) is a toxic element that can damage human organs. Determination of Cd in vegetables is often difficult because of low concentration and matrix effects. A simple, fast, flotation-assisted homogenous liquid–liquid microextraction (FA-HLLME) was developed for determination of Cd in vegetables prior to flame atomic absorption spectrometry (FAAS), in which 1-(2-pyridylazo)-2-naphthol (PAN) was used as a complexing agent. The process was carried out based on fast extraction of Cd from an acetic acid sample solution in which cyclohexane was the extracting solvent. Effects of pH, type and volume of extraction and homogeneous solvents, concentration of PAN, extraction time, and ionic strength on the extraction method were optimized. Under optimum conditions, the limit of detection and preconcentration factor were 0.6 µg·L −1 and 38, respectively. The relative standard deviation was less than 3.1%. Extraction recovery was 94.3%–100.9%.